Synthesis and Characterisation of Photo-Cross-Linkable Liquid Crystalline Poly(n-[n′-flurobenzoylstyryloxy]alkylmethacrylate)s and Their Fluorescence Lifetime Properties - G. Kumar; K. Subramanian; S. Ganesan (Journal of Spectroscopy)
This paper reports a study on photo-cross-linkable polymer containing pendant chalcone moiety exhibiting liquid crystalline as well as fluorescence lifetime properties in detail. The photoresponsive polymers were prepared, and their structure has been characterized by 1H-NMR, 13C-NMR, and UV-Visible spectroscopy. The photo-cross-linking behavior of polymers has been studied by UV-Visible and fluorescence spectroscopy. UV spectral studies revealed that the polymers follow 2π+2π cyclo addition reactions when they undergo photo-cross-linking under the influence of UV-light. Number and weight average molecular weight of the polymers were determined by Gel Permeation Chromatography (GPC) and polydispersity index value near to 1.5. The thermal and thermooxidative stability of the polymers were determined by Thermogravimetric Analysis (TGA). Thermal transitions were studied by DSC, and presence of mesophases was identified at 147 and 126∘C by hot stage polarized light optical microscopy (HPOM). Fluorescence lifetime measurements using the time-correlated single photon counting (TCSPC) method reveal that the average lifetime values decrease from 5.94 ns to 5.32 ns on UV-irradiation were discussed in detail.